Strengthening MSME Products Through Legal Compliance, Brand Management, and Improved Packaging Design: Penguatan Produk UMKM Melalui Pemenuhan Unsur Legalitas, Manajemen Merek, dan Perbaikan Desain Kemasan - Amallynda, Ikhlasul; Lukman, Muhamad; Garside, Annisa Kesy (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Pengabdian kepada Masyarakat (PkM) program is aimed at MSME business actors who receive assistance from the Malang district PDA, particularly those in the Lawang subdistrict and its surroundings. Currently, business actors are in the pre-startup (8.4%) and startup (32.7%) stages. This means that many small micro businesses have only recently begun or restarted operations following the COVID-19 pandemic. MSME actors face a variety of challenges, including difficulties in competing in the market, unfamiliarity with brand management and e-commerce strategies, a lack of MSME product legality permits, and a lackof good packaging label design. As a result, the opportunity for MSMEs to enter online and offline markets is being overlooked because industrial product quality cannot be separated from brand image and legal permits. The service program includes several activities, including dissemination of industrial product legality and standardization, assistance in submitting permits for the standard legality of industrial products, and assistance in creating product labelsand packaging designs.